Web tools selection in order to create learning activities in Cybermutua (2017)
Cibermutua is a cyber-museum developed for the Territorial Museum of the Northeastern Andes (Mutua), wich was designed as a space to know and explore the different urban, patrimonial and territorial realities of the Central-Eastern region of Colombia, contributing to the recovery of the cultural and urban heritage of the city of Tunja (Boyacá, Colombia). In order to reinforce the knowledge exhibited in the cyber-museum and generate interest among its users, digital learning activities were created that make use of free web tools. This article highlights the research process carried out in the selection of web tools for the creation of digital learning activities in the cyber-museum, presenting the results obtained during this process.